Effect of various biochars on physical, mechanical, and microstructural characteristics of cement pastes and mortars. (1st October 2022) - Haris Javed, Muhammad; Ali Sikandar, Muhammad; Ahmad, Waqas; Tariq Bashir, Muhammad; Alrowais, Raid; Bilal Wadud, Muhammad
Abstract: Using waste materials to replace a fraction of cement in concrete is economical and ecologically beneficial. In this work, cement pastes and mortars were fabricated with five different kinds of unsaturated biochars such as bagasse biochar (BB), coconut husk biochar (CHB), peanut husk biochar (PHB), rice husk biochar (RHB), and wheat husk biochar (WHB) at a dosage rate of 1-5 wt% relative to cement. The CO2 adsorption capacity of biochars was estimated to be in the range of 1.25–1.72 mmol/g. The influence of biochar addition on the setting time, water demand for normal consistency, compressive strength, water absorption, and apparent porosity of cement pastes and mortar was assessed. The analytical characterizations such as X-Ray diffraction (XRD), Fourier Transform infrared (FTIR), Scanning electron microscopy (SEM), and Raman spectroscopy analyses were employed for the analysis of biochar-based cement pastes. The results reveal that increasing the biochar dosage in cement pastes reduces setting time and increases the water demand irrespective of biochar type. The best results for water absorption, apparent porosity, and compressive strength were obtained at a dosage of 2 wt% relative to cement for each biochar. The analytical characterizations of biochar-based cement pastes showed the greater formation of hydration products leading to the development of a dense structure. The analytical results corroborated the mechanical performances. The efficacy of biochars in controlling the properties of cement pastes and mortars decreased in the order BB > RHB > PHB > CHB > WHB. Graphical abstract: Image 1 Highlights: Cement pastes and mortars were fabricated using various biochars. Biochars accelerate the hydration and reduce the setting time of cement pastes. Biochar improves mortar compressive strength by densifying the microstructure. Biochar cement pastes were characterized using SEM, XRD, EDX, Raman, and FTIR.